2011
DOI: 10.1111/j.1365-2621.2011.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of Rubus honey from the north-west of Spain

Abstract: A study of Rubus honey was conducted to determine their sugar composition, physicochemical properties, phenol and flavonoid contents, and sensorial and pollen characteristics. The principal pollen types present in the studied samples were Rubus, Castanea and Cytisus. Other pollen types such as Trifolium, some Erica sp., Eucalyptus or Echium were present in more than 50% of the pollen spectra. The sensorial characteristics of Rubus honey were amber-to-amber dark in colour, floral and ⁄ or vegetal olfactory perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
8
22
1
5
Order By: Relevance
“…Glucose and fructose values of the honey samples ranged from 19.2% to 31.8% and 25.4% to 39.2%, respectively, while the ratio of fructose to glucose was 1.1-1.5. Escuredo et al [17] reported glucose, fructose and the ratio of fructose to glucose values of thirty four samples belonged to Astragal honey (P<0.05). The highest and the lowest ratio of fructose to glucose belonged to Ziziphus (1.5) and Coriander (1.1) honeys, respectively.…”
Section: Electrical Conductivitymentioning
confidence: 94%
See 1 more Smart Citation
“…Glucose and fructose values of the honey samples ranged from 19.2% to 31.8% and 25.4% to 39.2%, respectively, while the ratio of fructose to glucose was 1.1-1.5. Escuredo et al [17] reported glucose, fructose and the ratio of fructose to glucose values of thirty four samples belonged to Astragal honey (P<0.05). The highest and the lowest ratio of fructose to glucose belonged to Ziziphus (1.5) and Coriander (1.1) honeys, respectively.…”
Section: Electrical Conductivitymentioning
confidence: 94%
“…[5,15] Total flavonoid content was measured by the absorbance at 415 nm using quercetin as the standard. [5,16,17] …”
Section: Physicochemical Analysesmentioning
confidence: 98%
“…[43] Average values of the studied honey samples were similar to the eucalyptus honeys described by Fernández-Torres et al, [44] although they were slightly higher than eucalyptus honeys described by González-Miret et al [42] Other honeys from Northwest Spain, such as Rubus honeys, had a similar content. [45] Honey is composed essentially of sugars. The most abundant sugars are fructose and glucose, followed by maltose and sucrose, while trehalose was only quantified in one sample and melezitose was not detected in any of the studied honeys (Table 4).…”
Section: Familymentioning
confidence: 99%
“…The mineral composition of the honey samples including K, Na, P and Zn were quantitatively determined using an atomic absorption spectrophotometer, after digestion by the wet ashing method (Escuredo et al, 2011).…”
Section: Determination Of the Mineral Compositionmentioning
confidence: 99%